Pengaruh Stres Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Melalui Motivasi Sebagai Variabel Intervening (Studi Kasus Swalayan Sari Mulya Pusat Limbangan, Brebes) - Tenaya Tenaya; Azizah Indriyani; Khalid Iskandar (Lembaga Pengembangan Kinerja Dosen, 2023)
Sari Mulya Supermarket is one of the supermarkets that provides various kinds of basic household needs and a place to shop that can shop wholesale and retail. This type of research uses quantitative. The population of this study with a sample of 60 employees as respondents. Data collection techniques by distributing questionnaires to respondents online using the Google form. The results of this study are that work stress has no partial and negative effect on employee performance. This is supported by the calculated t value for Job Stress (X1) on Employee Performance (Y), the calculated t value is -1.676 < t table 1.673 and the t test sig value for Job Stress (X1) on Employee Performance (Y) is 0.099 > 0, 05. Leadership style partially and positively influences employee performance. This is supported by the calculated t value for Leadership Style (X2) on Employee Performance (Y), the calculated t value is 5.081 > t table 1.673 and the t test sig value for Leadership Style (X2) on Employee Performance (Y) is 0.000 < 0.05 . Simultaneously Work Stress (X1) and Leadership Style (X2) are significant and positive on Motivation (Z). It is known that the significant value of Work Stress (X1) and Leadership Style (X2) simultaneously on Motivation (Z) is 0.000 < 0.05 and the calculated F value is 13.733 > F table 4.010. Simultaneously Work Stress (X1) and Leadership Style (X2) have a significant and positive effect on Employee Performance through Motivation (Z). It is known that the significant value of Job Stress (X1) and Leadership Style (X2) simultaneously on Employee Performance (Y) through Motivation (Z) is 0.000 < 0.05 and the calculated F value is 23.375 > F table 4.010.